Discovery of a novel EGFR ligand DPBA that degrades EGFR and suppresses EGFR-positive NSCLC growth - Yao, Nan; Wang, Chen-Ran; Liu, Ming-Qun; Li, Ying-Jie; Chen, Wei-Min; Li, Zheng-Qiu; Qi, Qi; Lu, Jin-Jian; Fan, Chun-Lin; Chen, Min-Feng; Qi, Ming; Li, Xiao-Bo; et al. (Signal transduction and targeted therapy, 2020)
Epidermal growth factor receptor (EGFR) activation plays a pivotal role in EGFR-driven non-small cell lung cancer (NSCLC) and is considered as a key target of molecular targeted therapy. EGFR tyrosine kinase inhibitors (TKIs) have been canonically used in NSCLC treatment. However, prevalent innate and acquired resistances and EGFR kinase-independent pro-survival properties limit the clinical efficacy of EGFR TKIs. Therefore, the discovery of novel EGFR degraders is a promising approach towards improving therapeutic efficacy and overcoming drug resistance. Here, we identified a 23-hydroxybetulinic acid derivative, namely DPBA, as a novel EGFR small-molecule ligand. It exerted potent in vitro and in vivo anticancer activity in both EGFR wild type and mutant NSCLC by degrading EGFR. Mechanistic studies disclosed that DPBA binds to the EGFR extracellular domain at sites differing from those of EGF and EGFR. DPBA did not induce EGFR dimerization, phosphorylation, and ubiquitination, but it significantly promoted EGFR degradation and repressed downstream survival pathways. Further analyses showed that DPBA induced clathrin-independent EGFR endocytosis mediated by flotillin-dependent lipid rafts and unaffected by EGFR TKIs. Activation of the early and late endosome markers rab5 and rab7 but not the recycling endosome marker rab11 was involved in DPBA-induced EGFR lysosomal degradation. The present study offers a new EGFR ligand for EGFR pharmacological degradation and proposes it as a potential treatment for EGFR-positive NSCLC, particularly NSCLC with innate or acquired EGFR TKI resistance. DPBA can also serve as a chemical probe in the studies on EGFR trafficking and degradation.